Review of Lower-Limb (Quasi-)Passive Exoskeletons for Human Augmentation - Tiancheng Zhou; Tianyun Li; Hongkuan Zhou; Wei Zheng (IEEE Access)
Researchers have been trying to develop lower-limb exoskeletons to reduce the metabolic cost for human augmentation. The research on (quasi-)passive exoskeletons has gained more widespread attention since the first passive ankle exoskeleton was demonstrated to reduce the metabolic cost of human walking in 2015. Here, we reviewed studies on lower-limb (quasi-)passive exoskeletons for human performance augmentation in the past decade and highlighted key innovations and techniques to enable some of these exoskeletons to achieve the goal of reducing metabolic cost. We reviewed the (quasi-)passive exoskeleton research from three aspects including biological fundamentals for exoskeleton design, assistive principle and mechanical design of exoskeleton, which are the primary considerations of designing and evaluating (quasi-)passive exoskeletons. Lastly, we underlined some practical challenges and emerging trends of (quasi-)passive exoskeleton technology for further enhancing human mobility performance in the future.